PENGARUH PIJAT REFLEKSI TERHADAP PENINGKATAN KUALITAS DAN KUANTITAS TIDUR PADA ANAK USIA PRASEKOLAH - Anggria Sari, Annisa; Jannah, Miftahul; Yuniftri, Astri (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2025)
Preschool children are in a period of change between infant and school age. Children start many activities at this age that can decrease the quality and quantity of sleep. Nowadays, children mostly sleep only 8-10 hours a day. Preschoolchildren need 11-12 hours a day to sleep. Lack of quality and quantity of sleep can decrease preschool growth and development in intelligence. This research aims to study the quality and quantity of preschool children. This study used a pre-experimental design. Samples were preschool children in the work area of the Tanjung Balai Karimun Health Center. The sample size was 7 children, recruited using purposive sampling. Data were collected through a questionnaire for quality and quantity of sleep and through observation to know the influence of reflection massage. The Wilcoxon Signed Rank Test analyzed quality data, and the Paired Sample T Test analyzed quantity data with a significance level of α <0,05. The results of this study revealed that there was a change in sleep quantity. There was also a change in sleep quality, but not significant. The Wilcoxon Signed rank test for sleep quality showed that α = 0,034. The Paired Sample T test for sleep quantity showed α = 0,003. From the results, we can conclude that a reflection massage influences/affects the quality and quantity of sleep. Reflection massage can increase the quality and quantity of sleep. The major function of reflection massage is stimulating the effector organ to decrease strain and relax the body. This condition is needed to get good quality and quantity of sleep. It concluded that reflection massage influences the increasing quality and quantity of children's sleep. Keywords : Preschool, Quality And Quantity Of Sleep, Reflection Massage